ENT 530 Social Media Portfolio: SY Sports / Mohamad Shahril Yazid - Yazid, Mohamad Shahril (2021)
Sportwear or activewear is clothes, including boots, used for sport or physical activity. Sportspecific clothing is worn for certain activities and physical fitness, for utilitarian, comfort or safety purposes. Typical sport-specific attire includes tracksuits, skirts, t-shirts and polo shirts. Specialized apparel covers swimsuits, wet suits, snow suits and leotards. Sports accessories include sneakers, baseball boots, riding boots and ice skates. The name of my company is SY SPORTS. The name of this website has been taken from my name, Shahril Yazid. The goods I run are more focused on athletic men's apparel only. Among the items that have been sold on my Facebook profile are soccer boots, tracksuits and soccer jerseys. My business address is No 386 Kampung Baroh Batu 31⁄4 Jalan Santan 01000 Kangar, Perlis. My company is based in my housing area because I want to make sure my business is going smoothly, and I can track it more closely. It can also carry my name to the communities and friends.